The Properties of Hydroxyapatite Derived from Carbonate Eggshell Waste Through Ball Milling and Heat Treatment Method - Raja Mohd Sonee, Raja Muhamad Ghouse; Ahmad Nawawi, Natasha; Shahedan, Noor Fifinatasha; S. Ramesh; Le Thi Bang (International Journal of Integrated Engineering, 2024)
Synthetic calcium phosphate, particularly hydroxyapatite (HA), has been used in various medical applications due to its biocompatibility and bioactivity. With time, increased interest in the development of HA from natural resources has started to emerge to produce more sustainable biomaterial precursors. HA has been successfully prepared from biogenic waste as the calcium precursor via extraction of calcium oxide from eggshells, seashells, and animal bones (cow, chicken, fish) via the wet method. The dry process, particularly solid-state reaction, has been least preferred due to the tendency of powder contamination and non-homogeneous powder mixing. However, with the proper processing regime, this method can produce pure HA on a mass scale with improved properties as it does not require precise control conditions. In this work, HA was synthesised from eggshell wastes through mechanochemical activation and heat treatment processes. The calcium precursor in pure calcium carbonate (CaCO3) was extracted from eggshells through calcination. Then, the Calcium Hydrogen Phosphate Dihydrate (DCPD) as phosphorus precursor was added to the calcined eggshells via a simple mechanochemical route for 2 hours, and the obtained powder mixture was subjected to heat treatment at 800°C to obtain pure HA. XRD analysis confirmed the formation of phase pure HA in the synthesised powder with an average crystallite size of 26.35 ± 0.1 nm and an average agglomerated particle size of 520 nm. Energy Dispersive X-ray (EDX) analysis has validated the elemental composition of synthesised HA with a Ca/P ratio of 1.76, which closely resembles pure HA with a Ca/P ratio of 1.67. Hence, through calcination, eggshell waste in pure CaCO3 form has been successfully utilised as a sustainable calcium precursor in producing HA via a dry method approach with high potential as a biomaterial for biomedical applications and has indirectly contributed to cost reduction of materials processing.